Physical activity and stress coping in the elderly - Fernando de Andréa; Fernanda Varkala Lanuez; Adriana Nunes Machado; Wilson Jacob Filho (Einstein (São Paulo), 2010)
Objective: To analyze the value of a physical activity program on stress coping of the elderly. Methods: Intervention study with a group of 18 elderly people referred by the Geriatric Service of Hospital das Clínicas of the Universidade de São Paulo, who attended a supervised exercise program, evaluated by the human activity profile and the coping questionnaire. Results: In the coping and functional performance scales, increased stress coping capacity and improvement of daily activities were found after exposure to a physical activity program. Conclusions: The practice of supervised and regular physical activity, combining aerobic, resistance, stretching, and respiratory exercises, yields positive effects in the coping capacity and in the accomplishment of the daily activities.